Estudio de factibilidad para la creación de una empresa dedicada a la prestación del servicio de soporte técnico de software y hardware, Positiva.Net, en la ciudad de Manizales (2014)
The main objective of this feasibility study comes from the need of people living in households and microenterprises that do not have a technical maintenance service 24 hours a day, seven days a week. This business idea has recently more opportunities to take advantage of, since the National Government in its National Development Plan established the Locomotive of Innovation, which includes the development and strengthening of ICT, which are intended to be used as cross-support to improve the country's competitiveness and promote regional development; providing computers to microenterprises and creating projects in order to have more households with internet access; which means that at any time the equipment will need maintenance. The provision of preventive / corrective service is focused on solving the symptoms described below: slow computing equipment, presence of viruses, no starting, no internet surfing, loss of information, software and / or hardware problems, peripheral equipment problems (monitor, printer, hard drive, mouse, keyboard), among other. These services will be provided where required by the customer, although due to the type of service and according to research, it is more likely to be delivered at home or remote support, it means at the usual workplace or home. According to market research, using as research theory the benchmarking, the technical maintenance service to be provided is I and II level, to 3 and 4 strata costumers, at a fair and rational price. The company's location will be in a 4 strata zone with public services availability and access to exclusive parking lots, giving security and confidence to customers.